Adaptive sports for promoting physical activity in community-dwelling adults with stroke: A feasibility study. (October 2021) - Nayak, Pradeepa; Mahmood, Amreen; Kumaran D, Senthil; Natarajan, Manikandan; Unnikrishnan, Bhaskaran; Solomon, John M.
Abstract: Background: Despite proven health benefits of regular participation in physical activities (PA), adults with stroke fail to achieve recommended levels of PA. Sports being an enjoyable activity is more likely to encourage participation. Therefore, the objectives of the present study are i) to develop and test the feasibility of adaptive sports for promoting PA and Quality of Life (QoL) in community-dwelling adults with stroke, and ii) to explore the participants perception and experiences of playing adaptive sports. Methods: Two focus groups were conducted among the eight experts and a person with stroke to develop adaptive sports. To test the feasibility of these adaptive sports, in a multi methods study eighteen community dwelling adults with stroke were recruited. Participants played adaptive sports twice a week for two months in a community center. Participants pre and post intervention PA levels and QoL were measured. Participants were also interviewed at the end of the program to explore their experiences of participation in adaptive sports. Results: At the end of the program retention rate of the participants was 83.33% and there was a significant improvement in PA levels, while the improvement in QoL was not statistically significant. Participants expressed positive experience with the program. There were no adverse events during or after the participation. Health benefits, fitness, and fun were reported as facilitators, while lack of access to the sporting facility and lack of caregiver support were reported as barriers to participation. Conclusion: Adaptive sports appear to be safe, feasible, and well accepted by the adults with stroke. Highlights: Adults with stroke demand modification of existing sports for the active participation. Adaptive sports are, safe, feasible, and well accepted by adults with stroke. Adaptive sports have the potential to improve physical activity levels in stroke. Health benefits, fitness, and fun were reported as facilitators for participation.